Screening for Informative Express Methods to Assess Spirulina Cyanobacteria Preservation in Cryopreservation - Grechishnikova, Mariia P.; Chizhevsky, Viktor V.; Govor, Iryna V.; Vysekantsev, Igor P. (Problems of Cryobiology and Cryomedicine, 2017)
Probl Cryobiol Cryomed 2017; 27(2):183.